A Monument to Medieval Syrian Book Culture The Library of Ibn ʿAbd al-Hādī - Hirschler, Konrad (Edinburgh University Press, 2019)
This book discusses the largest private book collection of the pre-Ottoman Arabic Middle East for which we have both a paper trail and a surviving corpus of the manuscripts that once sat on its shelves: the Ibn ʿAbd al-Hādī Library of Damascus.